INTEGRATED APPROACH TO THE ASSESSMENT OF NUTRITION STRUCTURE OF DIFFERENT SOCIO-DEMOGRAPHIC GROUPS OF POPULATION - Kurakin M.S. (Техника и технология пищевых производств)
The standard of living of the population in any country is determined by several criteria, the key one is nutrition. In the Russian Federation, there are a number of relevant normative and legislative documents, both presidential decrees concerning the organization of nutrition in different socio-demographic groups including children and the assessment of actual nutrition, including the state of diet nutritive value. The researches periodically conducted in the field of food hygiene clearly show the dependence of health level of individuals or groups of people on certain lifestyle factors, including deviations from the recommended standards of food consumption (the estimated share of the most susceptible population is 50.7 %). There is an obvious need to carry out work aimed at the study of actual nutrition of the population systematically. An integrated approach to the assessment of the nutrition structure is offered. It is based on the main principles of the Concept of optimal nutrition, a comprehensive structure assessment of diet nutritive value (including the caloric value and the content analysis of 18 different nutrients), the analysis of real energy consumption of a person, the corrective actions with the financial component, the application of original, duly registered computer programs: «Calculation of nutritive value of diets», «Energy consumption and health», «Calculation of the food density index». These programs provide an opportunity to comprehensively assess the diet nutritive value of different population groups, to determine the real need for proteins, fats and carbohydrates based on the calculated energy consumption, to calculate a number of important indices that determine person welfare. The use of software enables to considerably reduce the time of data processing, to improve the result accuracy and, ultimately, to conduct more productively researches of applied nature in the field of nutrition and food hygiene.